Impact of Board Certified Psychiatric Pharmacists on improving urinary tract infection antibiotic appropriateness at an acute psychiatric hospital - Hamad Mohammad Adam PharmD, BCPS; Williams Andrew PharmD, BCPP; Kneebusch Jamie PharmD, BCPS, BCPP; Butala Niyati PharmD, BCPP (American Association of Psychiatric Pharmacists, 2023)
Introduction: Urinary tract infections (UTIs) are one of the most common indications for antibiotic use; patients with psychiatric disorders have a greater risk for UTI compared with patients without these disorders. However, there is little guidance on how best to manage antibiotic therapy in psychiatric hospitals. This study assessed the impact of a Board Certified Psychiatric Pharmacist (BCPP)-driven guideline on managing UTI treatment in an acute psychiatric hospital. Methods: The guideline was developed by the psychiatric pharmacy team and distributed to internists, psychiatrists, and pharmacists. Preintervention data were assessed for patients admitted between November 30, 2019, and February 23, 2020; postintervention data were assessed from February 25, 2020, to April 24, 2020. All patients ages 13 years and older who were admitted and had orders for an antibiotic to treat a UTI were included in this study. Appropriate UTI management was defined as an appropriate agent, dose, route, and frequency per the treatment guideline. Additionally, the following criteria were to be ordered and assessed to be deemed appropriate: urinalysis, urine culture, complete blood count, basic or complete metabolic panel, temperature, and subjective symptoms. Results: Before intervention, 19.0% of antibiotic orders were appropriate; after intervention, 46.7% of antibiotic orders were appropriate (P = .048). Conclusion: The implementation of a BCPP-driven treatment algorithm was associated with a significant increase in appropriate antibiotic regimens for the treatment of UTIs in patients admitted to a psychiatric hospital.